Prevalence of work-related musculoskeletal disorders among dairy farmers in Malur Milk Co-operative society, Kolar District, Karnataka, India - Coates, Reubel; Malvika, Crispin; Alvina; Violet, Swati Dinesh; Ekka, Deepali; Gnanaselvam, Nancy A (International Journal of Occupational Safety and Health, 2023)
Introduction: The burden of work-related musculoskeletal disorders (WRMSDs) is high among dairy farmers, as they are involved in unacceptable working postures and movements. This study aims to assess the prevalence of WRMSDs and their associated factors among dairy farmers in Malur Milk Co-operative Society, Kolar District, Karnataka, India. Methods: A cross-sectional study was done from February 2022 to April 2022, among 150 dairy farmers aged 18 years and above. We collected socio-demographic, occupation, ergonomics and co-morbidities related details by administering a questionnaire. Assessment of musculoskeletal disorders was by Standardized Nordic Questionnaire and Mental health was assessed by Patient Health Questionnaire (PHQ-9). Results: The mean age was 40.96 13.49 years, and 66% of our study participants were males. The secondary occupation was agriculture(63%). Working hours per day was more than 8 hours in 19.3%. History of lifting heavy weights(78%), standing for long hours (56%) and sitting in squatting positions for long hours(66%) was present in this occupational group. The prevalence of WRMSDs was found to be 64.7%. The site of musculoskeletal disorders was found to be highest in the lower back (48.7%) and knees(45.3%). On multivariate analysis, belonging to the male gender [aOR = 0.33 (95%CI: 0.12-0.85)] and prolonged standing [aOR = 3.39 (95%CI: 1.46-7.89)] were the risk factors for WRMSDs. Conclusion: The prevalence of WRMSD is significantly high among dairy farmers in rural areas, affecting the lower back and knees predominantly. Education on ergonomics, routine physical activity, and accessibility to social security schemes will improve the health status of this community.